An integrated method of therapeutic lifestyle change for older adults with dyslipidaemia. (July 2017) - Zhao, J.-Y.; Li, H.; Jin, S.; Chen, X.-H.; Chen, L.-L.
Abstract: Objectives: To evaluate the effect of therapeutic lifestyle change with a non-pharmacological intervention method in older adults with dyslipidaemia. Study design: Stratified randomized trial. Methods: Participants with dyslipidaemia ( n  = 214) aged ≥60 years were randomized to the conventional guide group, the educational course (EC) group, the telephone call (PC) group or the PC + EC group for 24 weeks. Total cholesterol, triglyceride, low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and the knowledge, attitude and practice score for serum lipids were measured at baseline (T1), mid-intervention (week 12, T2) and post-intervention (week 24, T3). Results: Except the conventional guide group ( n  = 62), the PC group ( n  = 56), the EC group ( n  = 49) and the PC + EC group ( n  = 47) showed significant intra-group differences in serum total cholesterol, low-density lipoprotein cholesterol, triglyceride, high-density lipoprotein cholesterol and knowledge, attitude and practice score after the intervention. The improvements were most prominent and sustained over time in the PC + EC group at post-intervention. Conclusions: The PC + EC method is more efficient for improving serum lipids and enhancing health awareness than any single programme in older adults with dyslipidaemia. This overlapped therapeutic lifestyle change method may serve as a cost-effective adjunct and ensure the continuity of high-quality health services for patients with dyslipidaemia. Highlights: We found a basic technique model for improving patients with dyslipidaemia. It is beneficial for patients' life quality and attitudes towards chronic disease. The model has the advantage of controlling chronic disease among the elderly population. The gradual, multiple, overlapped effect is the typical treatment for dyslipidaemia.